School Performance among Children and Adolescents during COVID-19 Pandemic: A Systematic Review - Eleni Panagouli; Androniki Stavridou; Christina Savvidi; Anastasia Kourti; Theodora Psaltopoulou; Theodoros N. Sergentanis; Artemis Tsitsika (MDPI AG, 2021)
As a result of COVID-19 restrictions, conventional ways of schooling were not possible, and in order to continue the educational process new digital resources, such as online learning platforms, were imposed. Although virtual courses provided high-quality educational material, the efficiency in children's and adolescents' academic performance in general is yet to be known. The purpose of this systematic review is to examine whether the academic performance of school-aged students was impacted or not through online learning and modified educational methods during the ongoing COVID-19 pandemic. According to the studies, either students suffered from learning losses comparing to pre-pandemic years or, in some cases, they benefited from online learning, especially in mathematics. Younger students and students with neurodevelopmental disorders or special education needs seemed to suffer more. Parents/caregivers reported that their children's performance deteriorated, while others thought that online learning was beneficial. Teachers also reported that students presented academic gaps and difficulties in mathematics and reading compared to typical years. Consequently, the new ways of schooling imposed by the restrictions have not been fully tested and the impact cannot be described thoroughly. The investment in technological equipment in schools for the majority of students, along with the training of teachers in digital competence, should be a priority.